Improving carotenoid pigments production in Rhodotorula mucilaginosa using UV irradiation - Issa, S. (2018)
Rhodotorula yeasts were isolated from various local sources in Damascus, Syria, during 2012 and 2013. Fifty isolates (23 from leaves trees, 13 from different soils, 6 from different meats, 6 from dairy products, 1 pickle and 1 traditional sweet) were identified using API 20C AUX system. Isolated yeasts were classified into three Rhodotorula species: R. mucilaginosa, R. glutinis and R. minuta representing 76%, 20% and 4% of total isolates tested respectively. All isolates were able to produce carotenoid pigments that varied in their quantities ranging from 13.61 μg/g dry biomass for isolate A28 to 658.23 μg/g for isolate A23. The wild strain A23 of R. mucilaginosa was subjected to mutagenesis using UV irradiation at a wavelength of 254 nm. Highest carotenoid production within isolated mutants reached a value of 734.58 μg/g dry biomass after an irradiation period of 4.5 minutes. Overall, UV irradiation